A finite set-model predictive control based on FPGA flatform for eleven-level cascaded H-Bridge inverter fed induction motor drive - Mai Van Chung; Do Tuan Anh; Phuong Vu (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Model predictive control has been considered as a powerful alternative control method in power converters and electrical drives recently. This paper proposes a novel method for finite control set predictive control algorithm foran induction motor fed by 11-level cascaded H-Bridge converter. To deal with the high computation volume of MPC algorithm applied for CHBconverter, 7-adjacent vectors method is applied for calculating the desired voltage vector which minimizes the cost function. Moreover, by utilizingfield programmable gate array (FPGA) platform with its flexible structure,the total execution time reduces considerably so that the selected voltage vector can be applied immediately without delay compensation. This method improves the dynamic responses and steady-state performance of the system. Finally, experimental results verify the effectiveness of control design